Hepatic Metastasis as an Unusual Manifestation of Papillary Thyroid Carcinoma: A Rare Case Report (Bangladesh Journal of Nuclear Medicine, 2026)
Papillary thyroid carcinoma (PTC) is typically an indolent malignancy with a favorable prognosis, and distant metastases are uncommon, most frequently involving the lungs and bones. Hepatic metastasis from PTC is exceedingly rare and may present diagnostic and therapeutic challenges. We report a case of papillary thyroid carcinoma with hepatic and lymph node metastasis (LNM), highlighting its unusual presentation, diagnostic workup, and management approach in a 68-year-old woman with PTC with LNM further developed hepatic metastasis that was of thyroid origin, which was proven cytologically.Bangladesh J. Nuclear Med. 28(2): 371-373, 2025